Epidemiology of Kidney Cancer - D. Pascual; A. Borque (Advances in Urology)
Some tumors are known to have a definite cause-effect etiology, but renal cell carcinoma (RCC) is not one of them precisely. With regard to RCC we can only try to identify some clinical and occupational factors as well as substances related to tumorigenesis. Smoking, chemical carcinogens like asbestos or organic solvents are some of these factors that increase the risk of the RCC. Viral infections and radiation therapy have also been described as risk factors. Some drugs can increase the incidence of RCC as well as other neoplasms. Of course, genetics plays an outstanding role in the development of some cases of kidney cancer. Chronic renal failure, hypertension, and dialysis need to be considered as special situations. Diet, obesity, lifestyle, and habits can also increase the risk of RCC. The aim of this review is to summarize the well-defined causes of renal cell carcinoma.